Pollutants in Breast Milk: A Public Health Perspective – A Commentary of the Nutrition Committee of the French Society of Pediatrics. Issue 3 (27th March 2021) - Lapillonne, Alexandre; Bocquet, Alain; Briend, André; Chouraqui, Jean-Pierre; Darmaun, Dominique; Feillet, François; Frelut, Marie-Laure; Guimber, Dominique; Hankard, Régis; Peretti, Noel; Roze, Jean-Christophe; Simeoni, Umberto; et al.
Abstract : ABSTRACT: Pregnant and lactating women are continuously and ubiquitously exposed to numerous environmental pollutants from various sources including air, food, water, and occupational and household environments. The available evidence shows that pollutants are present in human milk and one of the emerging questions is what happens when the nursing infant is involuntarily exposed to contaminants through breastfeeding. The available literature does not currently provide a conclusive evidence of any consistent or clinically relevant health consequences in infants exposed to environment chemicals through breast milk. The available data strongly suggest that the benefits of breastfeeding outweigh the potential harmful effects of pollutants contained in human milk. The committee of nutrition of the French Pediatric Society strongly supports breastfeeding but also calls for public health actions to reduce the overall contamination level in the environment, to continue promoting breastfeeding, and to support research in this area.